ANALISIS PENERAPAN MANAJEMEN BERBASIS SEKOLAH PADA SEKOLAH DASAR DI GUGUS I KECAMATAN BLAHBATUH - Chindytia, Chindytia; Anak Agung Gede Agung; Ni Putu Suci Pramesti; I Gusti Agung Mastri Mahadewi Widyas Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of School-Based Management (SBM) in public elementary schools within Cluster I, Blahbatuh District. The research employs a quantitative descriptive approach with survey instruments covering seven management components: curriculum management, student management, human resource management, financial management, facilities and infrastructure management, public relations management, and excellent service management. The study involved 30 respondents drawn from school principals, teachers, and administrative staff across member schools in Cluster I, Blahbatuh District. Data collection used a dichotomous-scale instrument (1 = Yes, 0 = No) with 50 items per management component. Data were analyzed using descriptive statistics including mean, median, mode, standard deviation, and frequency distribution. The results showed that overall SBM implementation in these schools is in the very good category, with mean scores ranging from 46.57 to 49.93 out of a maximum score of Financial management received the highest mean (49.93) with the lowest standard deviation (0.25), indicating excellent and highly consistent implementation. In contrast, curriculum management recorded the lowest mean (46.60) and highest variability (SD = 3.22), while human resource management showed the largest range (15) and highest standard deviation (6.07), signaling meaningful implementation gaps. These findings suggest a need for more focused professional development in curriculum and human resource management to achieve uniform implementation quality across all management components.